PERAN KEPALA SEKOLAH DAN GURU PAI DALAM PENINGKATAN MUTU MELALUI MANAJEMEN BERBASIS SEKOLAH DI SMA MUHAMMADIYAH 3 SURAKARTA TAHUN PELAJARAN 2015/2016 - Muwahidah Nur Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2016)
Islamic Education should be able to follow the social changes in society. Islamic education should not isolate themselves from the realities of life that is constantly evolving and constantly changing in line with the development of human civilization. Within this framework, schools are required to have a strategy and tactics in managing Islamic education that one way the School Based Management. Principals and teachers as the main element in the implementation of the School Based Management should also be actively involved to make it happen. Accordingly, this study will examine the role of school principals and teachers to improve the quality of learning through school-based management in SMA 3 Muhammadiyah Surakarta. Through a qualitative descriptive methods obtained the results that the principal role in improving the quality of Islamic education through school-based management in SMA Muhammadiyah 3 Surakarta, namely as: leader, supervisor, educator, innovator and motivator. While the role of Islamic Education teachers in improving the quality of Islamic education through school-based management in SMA Muhammadiyah 3 surakarta the school year 2015-2016, namely; Providing motivation to students, using methods or strategies vary, following the improvement of teacher competency, assist students in religious extracurricular activities and provide guidance and role models to students.Keywords: school-based management , Islamic educationÂ and quality